Exploring technology integration challenges and coping strategies among social studies teachers - Öksüzoğlu, Muhammed Kürşat; Tünkler, Vural (Discover, 2026)
In the 21st century, expectations for technology integration in education have increased, making it a necessity in international standards and updated curricula. This study aims to examine social studies teachers’ experiences with technology integration in depth, focusing particularly on technostress, technostress coping strategies, and perceived school support. The study was conducted using a phenomenological design. The study group, selected through the maximum variation sampling method, consisted of five social studies teachers. Data were analyzed following Colaizzi’s phenomenological method. The findings indicate that the participants perceive technology integration as a pedagogical necessity and experience satisfaction when it contributes to student achievement. However, various barriers—such as technical infrastructure problems and insufficient technological pedagogical content knowledge (TPACK)—were found to cause technostress among teachers. The participants reported using a range of coping strategies, including seeking technical support from stakeholders, employing relaxation and time-management techniques, and enhancing their pedagogical and technological competencies. Notably, school support characterized by accessible technical assistance and supportive leadership was found to play a critical role in reducing technostress and sustaining technology integration efforts. Overall, the study emphasizes the need for continuous professional development, strong institutional support mechanisms, and a collaborative school culture to ensure effective technology integration in social studies education. © The Author(s) 2026.
Keywords: Coping strategies for technostress; School support; Social studies; Teacher; Technology integration; Technostress